Depositing Layers of Nano Graphene on P-Type Silicon Substrate and Studying the Structural and Optical Properties - Jasim, Marwan Muneam; Al-Tikrity, Shareef Faiq Sultan (Journal for Research in Applied Sciences and Biotechnology, 2023)
The present study involved the deposition of graphene films onto a silicon substrate of p-type using the Pulsed Laser Deposition (PLD) technique by varying the number of laser pulses (700, 600, and 500 pulses) at a fixed energy of 800 mj and a frequency of 6 Hz. The thickness of the prepared samples was calculated, revealing a significant increase in thickness (from 282 to 223 nm) attributed to the accumulation of material with increasing number of pulses. X-ray diffraction (XRD) patterns of graphene samples showed an increase in both the degree of crystallinity and the intensity of the graphene peak with increasing number of pulses leading to an initial boost in crystalline growth. The utilization of (SEM) images, particularly in samples created with 700 pulses, they appear to be more extended and smoother, forming wavy surfaces. Furthermore, a discernible augmentation in the quantity of graphene atomic layers was seen from 80 to 116 in samples that underwent an increase in the number of pulses from 500 to 700. The observation revealed a distinct arrangement of the surface, where, these layers effectively covered the surface with a thickness measuring 115 nm. Furthermore, a noticeable variation in the surface morphology of the deposited samples was also observed with increasing number of pulses. FTIR spectra exhibited a conspicuous augmentation in the intensity of bands, particularly for the asymmetric and symmetric vibrations of the CH2 group, which manifest at wavenumbers of 2940 and 2890 cm-1, respectively, concomitant with an escalation in the number of laser pulses employed during the deposition procedure.